2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6609466
|View full text |Cite
|
Sign up to set email alerts
|

Novel device to trend impedance and fluorescence of the cervix for preterm birth detection

Abstract: Preterm birth is the leading cause of worldwide neonatal mortality. It follows a pathologically accelerated form of the normal processes that govern cervical softening and dilation. Softening and dilation occur due to changes in cervical collagen crosslinking, which can be measured non-invasively by changes in tissue fluorescence and impedance. We present a novel device designed specifically to take fluorescence and impedance measurements throughout pregnancy, with the end goal of fusing and trending these mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The authors concluded that the device was not “sufficiently accurate to justify clinical use”, 43 although impedance is currently being investigated longitudinally with a novel device that can be worn like a pessary on the cervix. 44…”
Section: Quantifying Cervical Remodelingmentioning
confidence: 99%
“…The authors concluded that the device was not “sufficiently accurate to justify clinical use”, 43 although impedance is currently being investigated longitudinally with a novel device that can be worn like a pessary on the cervix. 44…”
Section: Quantifying Cervical Remodelingmentioning
confidence: 99%
“…Specific use of this device is described in Etemadi et al 12,13 . The mold used to create the intravaginal probe was fabricated from ABS430 material using a Dimension uPrint Plus 3D printer.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The mold and intravaginal probe in Figures 14 and 15 demonstrates representative results of the procedure presented in this article. Specific use of this device is described in Etemadi et al 12,13 . The mold used to create the intravaginal probe was fabricated from ABS430 material using a Dimension uPrint Plus 3D printer.…”
Section: Representative Resultsmentioning
confidence: 99%